2019
DOI: 10.7759/cureus.5663
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Extensively Drug-resistant Salmonella Typhi from a Tertiary Care Hospital in Pakistan

Abstract: Introduction: Since 2016, the province of Sindh is in the limelight because of its association with the emergence and spread of extensively drug-resistant Salmonella typhi (XDR S. typhi). Although its global spread has been proven in several studies, our information regarding its countrywide existence is still insufficient. In the last four years, few cases of XDR S. typhi were identified at the Shifa International Hospital (SIH), Islamabad, Pakistan. This article aims to report demographic patterns, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 13 publications
5
38
0
Order By: Relevance
“…Antibiotic resistance is a major problem in the management of enteric fever. MDR and XDR cases of enteric fever have been reported [5,11,12]. The largest outbreak of ceftriaxone-resistant S. typhi was reported in Pakistan during 2017-2018 [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibiotic resistance is a major problem in the management of enteric fever. MDR and XDR cases of enteric fever have been reported [5,11,12]. The largest outbreak of ceftriaxone-resistant S. typhi was reported in Pakistan during 2017-2018 [12].…”
Section: Discussionmentioning
confidence: 99%
“…One of these cases was tested for and found to be sensitive to azithromycin as well. A study conducted on XDR S. typhi in Northern Pakistan reported antibiotic sensitivity only to azithromycin and meropenem [11]. Yousafzai et al investigated the outbreak of ceftriaxone-resistant S. typhi in Hyderabad during 2016-2017 and reported a similar antibiotic sensitivity profile, that is, azithromycin, imipenem and meropenem [12].…”
Section: Discussionmentioning
confidence: 99%
“…6 But recent reports of XDR (chloramphenicol, amoxicillin, TMP, fluroquinolones and ceftriaxone) strains of Salmonella in areas of Sindh (Pakistan) have been alarming. 7,9,10 International Surveillance has also identified XDR strains in patients in UK, USA and Canada with all of them having travelled to Pakistan in recent past. 8,9 Pakistan health authorities have reported an outbreak of extensively (XDR) typhoid fever that begin in Hyderabad district of Sindh province in November, 2016.…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of XDR enteric fever in Hyderabad (7) and in Islamabad (14) revealed that 56% and 33% affected children were under 5 years of age. This nding is consistent with our study, since we found that the median age of affected children was 5 years (IQR: 2-8 years).…”
Section: Discussionmentioning
confidence: 99%